Cell cycle regulation of tubulin RNA level, tubulin protein synthesis, and assembly of microtubules in Physarum. - Schedl, T; Burland, T; Gull, K; Dove, W (1984)
The temporal relationship between tubulin expression and the assembly of the mitotic spindle microtubules has been investigated during the naturally synchronous cell cycle of the Physarum plasmodium. The cell cycle behavior of the tubulin isoforms was examined by two-dimensional gel electrophoresis of proteins labeled in vivo and by translation of RNA in vitro. alpha 1-, alpha 2-, beta 1-, and beta 2-tubulin synthesis increases coordinately until metaphase, and then falls, with beta 2 falling more rapidly than beta 1. Nucleic acid hybridization demonstrated that alpha- and beta-tubulin RNAs accumulate coordinately during G2, peaking at metaphase. Quantitative analysis demonstrated that alpha-tubulin RNA increases with apparent exponential kinetics, peaking with an increase over the basal level of greater than 40-fold. After metaphase, tubulin RNA levels fall exponentially, with a short half-life (19 min). Electron microscopic analysis of the plasmodium showed that the accumulation of tubulin RNA begins long before the polymerization of mitotic spindle microtubules. By contrast, the decay of tubulin RNA after metaphase coincides with the depolymerization of the spindle microtubules.